Novel optical microscopy techniques to assess grain orientation information in polycrystalline materials - Wang, Xiaogang (2018)
Optical microscopy is often used to characterize the surface microstructure of polycrystalline materials because of its simplicity and low-cost. However, the type of information acquired is limited by the diffraction barrier of optical lenses. For this reason, optical microscopy cannot be employed to resolve materials’ atomic structure and its use is typically limited to quantifying the geometry and distribution of the microstructural features that can be resolved, such as crystal grains, phases, and defect. In this project we will use modified optical techniques and develop novel numerical analysis methods to overcome the diffraction barrier of optical microscopy and assess grain orientation information. Our techniques rely on the quantification of reflected light intensity as a function of incident light direction or light polarization. Our results lay the foundation for the development of new optical-based techniques for cost-effective and high-throughput microstructure characterization of polycrystalline materials.